On the Ricardian Theory of Value: A Note - Pasinetti, Luigi L. (Review of Economic Studies, 1981)
Journal Article On the Ricardian Theory of Value: A Note Get access Luigi L. Pasinetti Luigi L. Pasinetti Università Cattolica, Milan Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 48, Issue 4, October 1981, Pages 673–675, https://doi.org/10.2307/2297210 Published: 01 October 1981 Article history Received: 01 April 1981 Accepted: 01 July 1981 Published: 01 October 1981